ERAD‐dependent control of the Wnt secretory factor Evi - Gläser, Kathrin; Voloshanenko, Oksana; Kranz, Dominique; Boutros, Michael (The EMBO journal, 2018)
Active regulation of protein abundance is an essential strategy to modulate cellular signaling pathways. Within the Wnt signaling cascade, regulated degradation of β‐catenin by the ubiquitin‐proteasome system (UPS) affects the outcome of canonical Wnt signaling. Here, we found that abundance of the Wnt cargo receptor Evi (Wls/GPR177), which is required for Wnt protein secretion, is also regulated by the UPS through endoplasmic reticulum (ER)‐associated degradation (ERAD). In the absence of Wnt ligands, Evi is ubiquitinated and targeted for ERAD in a VCP‐dependent manner. Ubiquitination of Evi involves the E2‐conjugating enzyme UBE2J2 and the E3‐ligase CGRRF1. Furthermore, we show that a triaging complex of Porcn and VCP determines whether Evi enters the secretory or the ERAD pathway. In this way, ERAD‐dependent control of Evi availability impacts the scale of Wnt protein secretion by adjusting the amount of Evi to meet the requirement of Wnt protein export. As Wnt and Evi protein levels are often dysregulated in cancer, targeting regulatory ERAD components might be a useful approach for therapeutic interventions. - Synopsis - - - - Wnt palmitoylation by O‐acetyltransferase Porcupine (PORCN) along the secretory pathway regulates the stability of the Wnt secretory factor Evi/Wls by protecting Evi/Wls from ubiquitination and degradation via the ERAD pathway in the endoplasmic reticulum. - - An increase in palmitoylated Wnt levels leads to Evi/Wls protein stabilization.In the absence of Wnt proteins, Evi/Wls is ubiquitinated by the E2‐conjugating enzyme UBE2J2 and the ubiquitin E3 ligase CGRRF1 and proteasomally degraded.An ERAD triaging complex consisting of PORCN and VCP/p97 regulates the levels of the Wnt cargo receptor Evi/Wls.In turn, higher Evi/Wls levels in the endoplasmic reticulum promote Wnt secretion.
Gesehen am 03.05.2019